(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fanissa F, Effendi MH, Tyasningsih W, Ugbo EN. 2022. Multidrug-resistant Salmonella species from chicken meat sold at Surabaya Traditional Markets, Indonesia. Biodiversitas 23: 2823-2829. Salmonella species is one of the major infectious pathogens associated with poultry birds, which also has an impact on public health. Antimicrobials are used as growth promoters or treatment of diseases thus; this encourages the persistent spread of antimicrobial resistance (AMR). This study aimed to identify multidrug-resistant Salmonella species from traditional chicken meat sold at Surabaya markets. A total of 150 chicken meat swab samples were collected from five different traditional markets and identified using microbiological standard methods. The Kirby-Bauer disk diffusion method identified multidrug-resistant Salmonella species on five different antibiotics discs. A low prevalence of Salmonella species was detected with a frequency of 11.3% (17/150). Some of the Salmonella isolates showed strong resistance to trimethoprim-sulfamethoxazole, tetracycline, aztreonam, and chloramphenicol. Five (29.4%) out of seventeen were multidrug-resistant Salmonella species. The presence of multidrug-resistant Salmonella species in these traditional markets is worrisome, since, it can lead to an outbreak of Salmonellosis as a result of the consumption of contaminated chicken meat. Therefore, the detection of multidrug-resistant Salmonella species is significant in understanding their prevalence and development of AMR. More strong awareness education and monitoring programs are recommended to mitigate the persistent spread of antimicrobial resistance.